Intérprete educacional cosmopolita : práticas heterotópicas na relação com a comunidade surda - Nogueira, Fernanda dos Santos (2018)
In Franz Pöchhacker, Community interpretation is the term coined worldwide for the type of interpretation that occurs in the educational, legal and medical context. In this dissertation, I resort to the dialogue between the studies from the perspective of Education and Translation Studies to problematize how the Community interpretation develops possibilities of understanding in the relations between the Educational Interpreter (IE) and the deaf community. In this work the specific objectives are: to understand IE practices and their relations with the deaf community; understand how the deaf community legitimizes the performance of this professional and their permanence in the community; and to problematize the effects of community interpretation on the relationship between IE and the deaf community. The methodological procedures have as theoretical reference Foucaultian when the narratives of the interviewees are assumed as confessions-narratives. IE capixabas were interviewed to access to what they say about their trajectories, acting as professionals, the forms developed to enter and remain in the community; and deaf subjects considered references in the deaf community of Espírito Santo to access how they understand and relate to this professional future in the community. From understanding of the sense of community, stranger and Community subject matter in Zygmunt Bauman, Alphonso Lings and Gert Biesta, I present the hypothesis that IE's relationship with the deaf community creates effects that place him in a desprestigied place when his it becomes a community matter, and not subject matter institutionalized. In the wake of Michel Foucault I present the possibility of thinking in other ways how the IE to relate to the community, when this professional happens to have a cosmopolitan attitude in creating spaces for the production of heterotopias in elaborating his own subjectivation, to govern himself , an attitude that allows us to think about the present, provoking transformations in oneself and problematizing what is instituted. It is the possibility of being a cosmopolitan educational interpreter with heterotopic practices in relation to the community.